Shaping Patient Loyalty through Quality Care: Analyzing Patient Satisfaction in Public Hospitals in Ghana - Francis Osei; Alfred Owusu; Collins Kankam-Kwarteng; Gertrude Agyemang; Joyce Dankwah Owusu (Research Synergy Foundation, 2024)
Public hospitals in Ghana face challenges such as limited resources and inconsistent care delivery, which impact patient satisfaction and loyalty. In this context, enhancing service quality is crucial for retaining patients and improving healthcare outcomes. This study investigates the role of service quality in shaping patient loyalty and explores patient satisfaction as a mediator in selected public hospitals in Ghana using the SERVQUAL model. A survey was conducted among 200 outpatients from five public health facilities in Kumasi, Ghana, between January and February 25, 2024. A quantitative methodology was applied to evaluate how patients' perceptions of service quality influence their loyalty toward public healthcare providers. In order to analyze the data, SPSS and the smart partial least square (PLS) software version 3.0 were used for structural equation modeling (SEM). The findings revealed that communication, the physical environment, and responsiveness significantly affect patient loyalty, whereas factors such as privacy, safety, and a customer-friendly atmosphere do not. Additionally, this study confirmed that patient satisfaction mediates the relationship between service quality and patient loyalty, underscoring the importance of service quality in enhancing both satisfaction and loyalty in health care. Based on these insights, this study recommends that health care institutions improve their service quality to strengthen public healthcare systems. The significance of this paper extends beyond regression analysis, as it also addresses the delayed effects of service quality on patient loyalty, considering both direct and indirect influences in the regression models.